Development of a reduced n-heptane-n-butylbenzene-polycyclic aromatic hydrocarbon (PAH) mechanism for engine combustion simulation and soot prediction. (15th December 2018) - Huang, Haozhong; Zhu, Jizhen; Lv, Delin; Wei, Yaopeng; Zhu, Zhaojun; Yu, Binbin; Chen, Yingjie
Abstract: A reduced n -heptane- n -butylbenzene-PAH mechanism consisting of 111 species and 542 reactions was developed for diesel engine combustion and soot modeling. The reduced mechanism was formulated based on a detailed n -butylbenzene (BBZ) mechanism and a published reduced n -heptane-PAH mechanism. The reduced BBZ sub-mechanism was constructed using the directed relation graph with error propagation, sensitivity analysis, reaction pathway analysis and rate of production analysis methods. An evaluation system of the most sensitive reactions was proposed and sensitivity coefficient maps of ignition delay were depicted for the optimization of the proposed mechanism. The present mechanism was extensively validated with experimental results of ignition delay in shock tubes and rapid compression machines, species concentration in premixed flames and jet stirred reactors, laminar flame speed, and with new direct injection compression ignition engine combustion and emission data. The results of prediction are in good agreement with experiments and suggest that the proposed mechanism can be applied for combustion and soot predictions in engines. The soot particle size distribution of BRF30 (30%BBZ+70% n -heptane in volume) is closer to D100 (real diesel) than TRF20 (20%toluene+80% n -heptane in volume). It is indicated that BBZ may be more appropriate as the representative of aromatic compounds than toluene in diesel surrogate fuels. Highlights: A reduced n -heptane- n -butylbenzene-PAH mechanism was developed for engine simulations. The final reduced mechanism includes 111 species and 541 reactions. An evaluation system of the most sensitive reactions was proposed for the optimization. The proposed mechanism was well validated with various experimental data. n -Butylbenzene is more appropriate as the representative of aromatic compounds than toluene.